2009
DOI: 10.1016/j.rmed.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary analysis of sex and gender in relation to the pathogenesis of bronchial asthma

Abstract: Some disagreements regarding the patho-physiology, diagnosis, treatment and prevention of asthma still prevail. Nevertheless, in order to better appreciate its complexity, openness to and persistent consideration for interdisciplinary as well as sex- and gender-related factors is required of the medical-research community in future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 140 publications
0
16
0
Order By: Relevance
“…Regarding this, there are neither earlier reports by which to prove two sub-types of alpha adrenergic receptors in the airways smooth musculature nor are there reports on the effects of clonidine in the receptors of smooth musculature [23]. Previous researchers have shown that there are no alpha-2 adrenergic receptors in the respiratory epithelia surface [18]. Recently, experiments conducted in vivo show that clonidine intermediates an inhibitory control over the activity of vagal excitation [24].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding this, there are neither earlier reports by which to prove two sub-types of alpha adrenergic receptors in the airways smooth musculature nor are there reports on the effects of clonidine in the receptors of smooth musculature [23]. Previous researchers have shown that there are no alpha-2 adrenergic receptors in the respiratory epithelia surface [18]. Recently, experiments conducted in vivo show that clonidine intermediates an inhibitory control over the activity of vagal excitation [24].…”
Section: Discussionmentioning
confidence: 94%
“…Existance of these receptors and their role in healthy and people ill from bronchial asthma and chronic obstructive bronchitis is not fully clarified. In the mechanism of lung obstructive diseases and bronchial asthma modulator substances, released after the inflammatory processes, have an important role, as do other substances released following the process of de-granulation of mastocyte [18].…”
Section: Discussionmentioning
confidence: 99%
“…There are some anatomical differences in the upper airways between males and females [19]; therefore, pharmaceutical aerosols are more likely to deposit in the upper airways in females than in males. Furthermore, the maximal inspiratory mouth pressure is significantly lower in females than in males [2], suggesting the potential risk of local deposition of DPI in females. In this study, we confirmed that the absence of gargling or mouth washing after inhalation is a risk factor in females treated with DPI, but not pMDI.…”
Section: Discussionmentioning
confidence: 97%
“…A number of recent studies have found sex and gender differences in the pathogenesis and clinical features of asthma [1,2]. Females are more likely to suffer from allergic asthma, have difficulty controlling asthma symptoms and exhibit adverse effects to drugs [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation